Influence of Learner Related Variables on Academic Performance: A Case of Public Primary Schools in Mathira, Nyeri County, Kenya - Githui, P. (African Journal of Education,Science and Technology (AJEST), 2019)
The Government of Kenya has invested heavily in terms of human and monetary resources in the primary education system in an effort to ensure that all children are provided with access to quality education. Despite this noble undertaking, the academic performance among primary school pupils in Mathira, Nyeri County, has remained dismal. Several studies that have been conducted in the area have focused on instructional resources, school and home factors and ignored the contribution of learner characteristics as a possible causal factor to the poor academic performance. This study assessed the contribution of pupil related variables on academic achievement in public primary schools in Mathira Constituency, Nyeri County, Kenya. The objectives of the study were to; analyze learner variables that influenced academic achievement and to find out the relationship between learner variables and academic achievement in public primary schools. It had been hypothesized that there was no statistically significant relationship between learner variables and academic achievement among learners in public primary schools. The study was informed by the Social Cognitive Theory (SCT) propounded by Albert Bandura, and adopted an ex post facto descriptive survey design. The population of the study consisted of 104 head teachers in public primary schools in Mathira Constituency, Kenya. Simple random sampling using Gay (2000) 10-30% was used to select the sample which yielded 31(30%) head teachers. Data was collected through a questionnaire that consisted of 8 items administered to the sampled head teachers. Internal consistency of the instrument was ascertained using Cronbach alpha which yielded a coefficient of 0.817. Data analysis was done using descriptive and inferential statistics. The study established that pupils failed to complete assignments, truancy was rare, learner motivation was low, most parents did not assist in homework and the pupils’ ability to engage in self-directed learning was limited. Regression analysis revealed that academic achievement in primary schools had a lot to do with; pupil failure to complete assignment, parents’ assistance in assignment and pupil motivation. Based on these findings, the study recommended the need for education stakeholders to put in place measures to ensure that parents assist their children with homework, promote pupils’ self-directed learning skills, and counsel pupils on negative peer pressure.